Gambaran dan faktor yang berhubungan dengan penggunaan gigi tiruan pada penduduk usia lanjut di Desa Selemadeg, Kabupaten Tabanan, Bali - I Gede Kayika Pradnya Utama; Putu Lestari Sudirman; Ketut Suarjana (School of Dentistry Faculty of Medicine Udayana University, 2018)
Background: As aging, there is also a degenerative process in the function of the body, especially teeth and mouth. One of this problem is tooth loss that can affects the function of the oral cavity. Aim: The purpose of this study is to know the factors related to the use of denture, among elderly people in Selemadeg. Method: Descriptive study used with cross sectional study, that be done in Selemadeg with 70 samples, obtained by simple random sampling. Data of this research obtained from interviews with the questionnaire. Data were tested using Chi-square test (p<0,05). Results: The result of this study showed the use of denture on elderly people in Selemadeg village are 12 people (17,1%). The use of denture based on economic status is above UMK (75%), with p value <0,001. Based on knowledge is the majority of respondents have a high level of knowledge (91,7%), with p value <0,001. Based on the experience is most of respondents had a good experience (58,3%), with p value <0,001. Conclusion: It was concluded that the use of denture among elderly people in Selemadeg village tends to be low, and based on economic status, knowledge, experience, and availability of time had statistically significant trend.